Proceedings of the ACM SIGIR International Conference on Theory of Information Retrieval 2017
DOI: 10.1145/3121050.3121074
|View full text |Cite
|
Sign up to set email alerts
|

The Positive and Negative Influence of Search Results on People's Decisions about the Efficacy of Medical Treatments

Abstract: People regularly use web search engines to investigate the efficacy of medical treatments. Search results can contain documents that present incorrect information that contradicts current established medical understanding on whether a treatment is helpful or not for a health issue. If people are influenced by the incorrect information found in search results, they can make harmful decisions about the appropriate treatment. To determine the extent to which people can be influenced by search engine results, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 8 publications
2
50
1
Order By: Relevance
“…In the case of searches on health, the biases that can occur are determinant for users, as one of the problems detected when consulting Dr. Google is that the more you look for the less you trust the doctor (Van-Riel et al, 2017). Regarding the effects of search results users find, we must bear in mind that these have a great influence on decision making (Pogacar et al, 2017) and that the dominant response can be decisive (White, 2014).…”
Section: Dr Google: Biases and Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of searches on health, the biases that can occur are determinant for users, as one of the problems detected when consulting Dr. Google is that the more you look for the less you trust the doctor (Van-Riel et al, 2017). Regarding the effects of search results users find, we must bear in mind that these have a great influence on decision making (Pogacar et al, 2017) and that the dominant response can be decisive (White, 2014).…”
Section: Dr Google: Biases and Effectsmentioning
confidence: 99%
“…The specific weight of search results is avoided when the user has prior scientific knowledge of the treatment on which information is sought on the Internet (Pogacar et al, 2017). Likewise, it also depends on the level of conviction of this prior knowledge and the reliability that the source that is being consulted suggests to the user (Kammerer et al, 2013).…”
Section: Dr Google: Biases and Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results offered can be unreliable [2], inaccurate [9], or of poor quality [34]. This can have a greater or lesser impact depending on the context [37], but is especially sensitive when it comes to health-related content, as Pogacar et al [31] showed in a recent study.…”
Section: Introductionmentioning
confidence: 99%